The Long Journey of Indonesian Science and Technology Policy during The New Order Period (1968-1998) - Maulana Akbar; Syifa Naufal Qisty; Veni Robiatal Adawiyah; Wisnu Mahardhika Putera (STI Policy and Management Journal, 2022)
This study examined Indonesia's science and technology (S&T) policies from 1966 to 1998. The research investigated how the government identifies S&T problems, plans policies, and implements policies to support S&T development using the primary source of national development planning, the six-volume Five-Year Development Plan (Repelita). This study contends that during the 32-year New Order regimes of Indonesian S&T policy, the focus of development shifted from agriculture to efforts to transition mastery of technology products through the development of Human Resources in Science and Technology (HRST), institutional development of S&T, implementation of S&T culture in government institutions, provision of S&T for industry, and technology transfer. Although Indonesian S&T development has never reached the peak where it can compete with developed countries, it does contribute to the creation of a foundational S&T ecosystem, particularly as the initial foundation for the next regime